Perlindungan Negara Dalam Menghadapi Corona Virus (Covid 19) Berdasarkan Hukum Tata Negara Darurat - Sudrajat, Shinta Azzahra; Kurniawan, Nandang Pamungkas (LPPM Universitas Harapan Bangsa, 2023)
The purpose of making this journal is to find out the development of Covid-19 in Indonesia and its impact on people's lives and how the steps taken by the government to deal with the Covid-19 Pandemic based on a study of emergency constitutional law, which using normative legal research methods were concluded according to Indonesian Emergency Constitutional Law, the Indonesian state recognizes emergency conditions with two terminologies, namely a state of danger and matters of compelling urgency. Regarding the Covid-19 pandemic from the perspective of this emergency constitutional law, and looking at the policies and legal instruments stipulated by the President, it can be concluded that the President does not categorize Covid-19 in the category of danger but enters the second terminology, namely urgency which compels according to with article 22 of the 1945 Constitution. Indonesia is now in a state of emergency as stated in Presidential Decree Number 11 of 2020. This difficult condition requires appropriate policies as progressive and responsive efforts in accordance with statutory provisions. In these difficult times, every policy is sure to reap a variety of responses, both based on the form of support and rejection. Keywords: Constitutional law, emergency, covid-19.